POLITICAL INNOVATION AND TURKEY (Third Sector Social Economic Review, 2018)
The concept of political innovation has produced different arguments and findings in the prevailing international literature and has proved to be a topic of much debate over the past two decades. However, existing research on the conceptualization of political innovation and its reflections in Turkish literature are, at present, far from satisfactory. Given the concepts of innovation and social innovation briefly, this study aims to both raise awareness on the concept of political innovation within the wider consideration of international literature, and suggest an assessment with samples from Turkish politics centered on a variety of political innovations. In the existing literature, three basic types of political innovation are observed which are in sequence (1) political innovation as the innovation of political institutions, (2) political innovation as the innovation of politics and political processes (3) political innovation as the innovation of political programs and policies. The conceptual analysis is to be carried out on three basic connotations of political innovation and will be shaped through the innovation of political processes, political approaches, and policies. While Turkish politics may appear to be conceptually unfamiliar with political innovation, Turkey can pose as a vivid and permanent political innovation case.
Keywords: political innovation; public innovation; political discourse